Improving the process to reduce ophthalmologic surgery cancellation and patient complaints - Padoveze, Maria Clara; Fornazari de Oliveira, Denize; Russo, Christiane; Azevedo de Faria, Rosaura Antonieta; Lino, Mariza; Fraga Penteado, Maria de Lourdes; Franzoloso Santos Martins, Mirian; Paula, Ana; Heli Zanoveli Santos, Neuza; Melo, Silvia Elaine; M. Carvalho, Keila (O Mundo da Saúde, 2010)
This study aims to describe a quality intervention program to reduce the rates of ophthalmologic surgery cancellation and patient complaints. Methods: the study was carried out at a university hospital in the state of Sao Paulo, Brazil. The intervention occurred from July to December, 2007. The methodology applied was based on the model of process improvement. A multidisciplinary work group was set up, composed of professionals from all stages in the line of surgical care and coordinated by the Quality Program staff. The goals of the project were: to reduce the rate of surgery cancellations and to reduce the number of patient complaints. An action plan was established based on the assessment of the main causes of the problems. The tools used included the worksheet 5W2H and a formal contract for the project. The rates of surgery cancellation before and after the intervention were compared using the chi square test and significance was assumed if P was less than. 05. Results: in the baseline period (2004-2005) the monthly rate of surgery cancellations ranged from 32 to 45%. In the year 2006 this rate increased from 38 to 66%. The main causes for surgery cancellations were: patient absence (33%), faults in surgical product provision (32%) and unpropitious clinical conditions (15%). Patient absence was reduced through improvement of communication between resident surgeons and the social workers team. Modifications were achieved in the provision chain for essential surgical products (intraocular lens, balanced salt solution, viscoelastic solution) and there was no more surgery cancellation caused by fault in product provision. Although there was no change in the overall rates of surgery cancellation between the baseline period (37%) and the intervention period (38%), the rates decreased compared to the year 2006 (51%) (P = 0.0001; RR: 0.75; IC: 0.71-0.78). The main cause of patient complaint was surgery cancellation; the physician-patient relationship was the object of many complaints. Specific training to improve this relationship was implemented. Patient complaints dropped from up to 20 in 2006 to about 10 per month in 2007. Conclusion: the methodology for process improvement showed to be useful in reducing the main causes of surgery cancellation and patient complaints. The work group expressed a high level of satisfaction regarding the methodology applied and the goals achieved.